Pengaruh Pembelajaran STEAM Terhadap Kemampuan Berpikir Kritis Pada Muatan IPA Kelas IV - Riantika, Anatasia; Nugraheni, Anita; Suryani, Desy; Nisa, Ana Fitrotun (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan Univers, 2024)
This study aims to determine the effect of STEAM (Science, Technology, Engineering, Arts, and Mathematics) learning on critical thinking skills in the fourth grade science content. This research is a quantitative approach with a Quasi Experimental Design type of research using Post-test Only Control Group Design. The population in this study was class IV with two classes. The samples taken were class IV A as the experimental class and class IV B as the control class. This research technique uses non-probability sampling with a purposive sampling technique. The data collection method used is an instrument in the form of a critical thinking test sheet. Using the statistical analysis method with the formula used is the Mann-Whitney U Test which was carried out with the help of the SPSS vs 26 application program. Based on the results of the study using the Mann-Whitney U test, it showed that the results obtained were the Sig. of 0.000. From these results it can be seen that Ho is rejected and Ha is accepted. It means that it can be concluded that there is an effect of learning STEAM (Science, Technology, Engineering, Arts, and Mathematics) on Critical Thinking Ability in the science content of Energy Sources grade IV.